2014
DOI: 10.5588/pha.14.0065
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of stigma associated with tuberculosis in Mexico

Abstract: Background Stigma is a major barrier to health care access and impacts the quality of life for individuals affected by tuberculosis (TB). Assessing TB stigma is essential to addressing health disparities. However, no such instrument was available in Mexico at the time of our study. This study examined the adaptability of the TB and human immunodeficiency virus (HIV) stigma scales previously used in Thailand. Methods The original scale, developed in English, was linguistically adapted to Spanish and administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 17 publications
4
30
1
3
Order By: Relevance
“…Similar to other studies [24,26,31,51], the current study found that the association of TB and HIV infection/AIDS increases TB stigma. Items such as 'Some people who have TB are worried about having AIDS" were rated highest.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to other studies [24,26,31,51], the current study found that the association of TB and HIV infection/AIDS increases TB stigma. Items such as 'Some people who have TB are worried about having AIDS" were rated highest.…”
Section: Discussionsupporting
confidence: 91%
“…While these were delivered as form of treatment, the real intention was to isolate people from the rest of the population to prevent disease transmission [46]. Evidence has shown that perceived risk of transmitting TB to the healthy community members is a leading cause of stigmatization in other settings [2,14,31,[47][48][49]. The current study shows that, in an attempt to deal with the risk of infecting others, the patients avoided sharing meals and kitchen dishes, sharing a room, and having sexual relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Although the rates were low, they could have affected preventive activities. Such attitudes could be due to feelings of guilt and shame [20]. Loss of job scored a low level of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, tuberculosis stigmatized individuals have negative impact on their self-esteem (Moya, Biswas, Chavez Baray, Martínez, & Lomeli, 2014). Disclosure of stigma can provide the opportunity to express hidden thoughts, feelings and emotions with those closest to you.…”
Section: Purpose Of the Studymentioning
confidence: 99%